0195 Mentorship in digital healthcare and implementation: A educational package to be piloted within hull and east yorkshire nhs trust. (2nd November 2015) - Gopal, Alan; Osuri, Pranav; Simpson, Mark
Abstract : Background and context: Digital healthcare is a contentious issue across the NHS, with great variations across Acute Trusts and other UK healthcare providers 1 despite the drive towards a paperless NHS by 2018. 2 The adoption of Electronic Patient Records (EPR) is seen as a key step to the realisation of a truly integrated health service, 3 theoretically improving patient safety and care quality. 4 The implementation of a new EPR system across Hull and East Yorkshire NHS Trust presents an excellent opportunity to observe and contribute to digital change at a regional level. Currently there are no defined educational programmes/opportunities for clinicians at a younger stage of their careers to be involved in digital healthcare, hindering the discovery and development of future drivers of digital healthcare in the UK. Methodology: We intend to capitalise on the opportunity provided by designing and piloting a 2 year mentorship in digital healthcare and implementation from July 2015, and disseminating it as an educational package for adoption by other healthcare providers. To our knowledge this venture is the first of its kind in the UK. The aim is to foster insight and engagement in digital health at a local level, encouraging action-based education 5 with senior supervision to benefit the Trust, supervisor and junior doctor/medical student. 6 Anticipated outcomes: The mentorship will empower and develop mentees 7 in digital change, enabling acquisition of an understanding of core principles underpinning digital healthcare and implementation through observation and engagement with the Technology and Innovation Centre within the Trust, including the successful completion of a digital healthcare project. Potential impact: Junior-driven initiatives have the potential to advocate, raise awareness and supplement change in a positive way. 8 Early acquisition of knowledge and skills in digital healthcare will increase potential benefits to the region and profession during the course of their careers. References: EHI Intelligence. The Clinical Digital Maturity Index. EHI Intelligence. Report number: 01, 2013 TechUK. Digitising the NHS: One Year on. TechUK. Report number: 01, 2014 Vikkelso S. Scand J Inform Sys . 2005;17(1):3–30 Boonstra A, Broekhuis M. BMC Health Serv Res. 2010;10 :231 Rasmussen EA, Sorheim R. Technovation 2006;26(2):185–194 Lamki N, Marchand M. Sultan Qaboos Univ Med J. 2006;6(1):6–12 Gawer A, Cusumano MA. Platform leadership and complementary innovation. In: Gawer, Cusumano MA, eds. Platform leadership . 2nd edn. Boston, MA: Harvard Business School Press, 2002: 1-14 Chew D, Jaworsky D, Thorne J, et al . Med Teach 2012;34(5):398–403